Village and Industrialization Study of social change in Modopuro Village, Mojokerto, Indonesia - Endik Hidayat; Aufa Izzuddin Baihaqi; Daniel Susilo (Nusantara Science and Technology Proceedings, 2022)
This research was conducted in Modopuro Village where the community experienced changes in their livelihoods due to the presence of new economic sources. The research question to be answered in this article is what are the impacts of duck farming activities and home industries in Modopuro Village? The unit of analysis to elaborate on this problem is the theory of social change. This study uses a qualitative method with the type of descriptive research. Collecting data from interviews with informants consisting of village heads, village officials, and the community. The results of this study found that changes in the livelihoods of the Modopuro village community had an impact on aspects of economic income sources and environmental pollution. In the economic aspect, the income of the villagers changed from the agricultural and livestock sectors to the micro-industry of chicken slaughterhouses and chicken intestine chip production. There are also environmental impacts, such as being polluted by running rivers and agricultural land due to the waste resulting from these business activities. The theoretical implication of the research findings is the verification of Lauer's concept of social change regarding aspects of Modopuro's social change due to capital factors, industrialization of technological developments in the marketing of Modopuro's superior products, and village bureaucracy that supports community empowerment activities in Modopuro village.